Retreatment with sofosbuvir and simeprevir of patients with hepatitis C virus genotype 1 or 4 who previously failed a daclatasvir‐containing regimen. Issue 6 (10th March 2016) - Hézode, Christophe; Chevaliez, Stéphane; Scoazec, Giovanna; Soulier, Alexandre; Varaut, Anne; Bouvier‐Alias, Magali; Ruiz, Isaac; Roudot‐Thoraval, Françoise; Mallat, Ariane; Féray, Cyrille; Pawlotsky, Jean‐Michel
Abstract : Failure to achieve sustained virological response (SVR) with hepatitis C virus (HCV) direct‐acting antiviral‐based regimens is commonly associated with emergence of resistance‐associated variants (RAVs). To avoid cross‐resistance, recent guidelines recommend that patients who have failed on nonstructural protein 5A (NS5A) inhibitors should be retreated with sofosbuvir (SOF; NS5B inhibitor) combined with simeprevir (SIM; protease inhibitor [PI]); however, supporting evidence is lacking. This "real‐world" study comprised patients who had failed to achieve SVR on previous NS5A‐based therapy with daclatasvir (DCV) plus pegylated interferon (Peg‐IFN) and ribavirin (RBV), with (n = 3) or without (n = 13) asunaprevir (ASV; PI). All 16 patients were retreated for 12 weeks with SOF plus SIM, without RBV. Antiviral efficacy was evaluated using the primary endpoint of SVR12 (SVR 12 weeks post‐treatment); on‐treatment response was also assessed. Patients (N = 16; 13 male; mean age: 54 years [range, 43‐73]) were chronically infected with HCV genotype (GT) 1 (1a, n = 11; 1b, n = 3) or 4 (n = 2); they had advanced fibrosis or compensated cirrhosis (FibroScan, 9.6‐70 kPa; cirrhosis, n = 9); median baseline HCV‐RNA level was 1.38 × 10 6 IU/mL. No patient discontinued treatment because of adverse events or virological failure. All patients achieved HCV RNA below lower limit of quantification (<12 IU/mL) by end of treatment (EOT) and 10 of 16 had a rapid response (week 4). SVR12 was achieved by 14 of 16 patients; the remaining 2 relapsed by 4 weeks post‐EOT (both were GT 1a infected with cirrhosis; 1 had previously failed DCV‐ASV plus Peg‐IFN and RBV). Presence of SIM RAVs/polymorphisms (R155K and Q80K) at study baseline did not predict retreatment failure. Conclusion: Our findings support the concept of retreating NS5A inhibitor failures with SOF combined with SIM. However, the most difficult‐to‐cure patients may need more than 12 weeks of treatment and/or the addition of RBV. (Hepatology 2016;63:1809‐1816)